Aquatic Toxicology Notes: Predicting the Fate and Effects of Aquatic and Ditchbank Herbicides - Chris Wilson (EDIS)
The purpose of this document is to introduce readers to: 1) factors affecting the exposure of aquatic organisms to aquatic herbicides, and 2) useful methods for estimating potential risks of acute mortality for non-target aquatic organisms. This document is SL236, a fact sheet of the Soil and Water Science Department, UF/IFAS Extension. Original publication date April 2006.